Mixed Virtual Supports Startup Survival During Pandemic: [Mixed Virtual Mendukung Keberlangsungan Startup Selama Pandemi] - Fadillah, Rafika; Helmi, Avin Fadilla (ANIMA Indonesian Psychological Journal, 2022)
The virtual team has been one of the solution strategies implemented by startups during the pandemic, in order to reduce virus spread (through physical and social distancing). The number of startups in Indonesia has been a great window of opportunity, however many startups have failed in the first year of operations, with the synergy of the teams being one of the principle causes. Unfortunately, studies on startup virtual teams in Indonesia are still lacking in portraying this situation. This study answers regarding the dynamics on startup virtual teams during the pandemic, with the aim of exploring the processes which took place within the startup virtual teams. The method used was that of convergent parallel mixed-methods, with the analysis of quantitative data from the questionnaires completed by 156 startup virtual teams, and of qualitative data from interviews conducted with five leaders of startup virtual teams. The study results indicated that the interaction of the teams was in mixed virtual form, i.e., the team interaction was performed not entirely online. Startup virtual teams during the pandemic conducted direct face-to-face interactions, prior to any virtual interaction, and/or were able to conduct face-to-face meetings during the pandemic, by paying attention to health protocols. These mixed virtual interactions created informal relationships, which supported the startups’ survival through the pandemic. Tim virtual merupakan salah satu strategi solusi yang dilakukan startup ketika pandemi demi menurunkan penyebaran virus (melalui physical and social distancing). Besarnya jumlah startup di Indonesia menjadi peluang besar, namun banyak startup yang gagal dalam satu tahun masa operasi pertama, dengan sinergitas tim sebagai salah satu penyebab utamanya. Sayangnya, studi mengenai tim virtual startup di tengah pandemi di Indonesia masih kurang memadai dalam mengambarkan kondisi tersebut. Studi ini menjawab bagaimana dinamika tim virtual startup di masa pandemi, dengan tujuan mengeksplorasi proses yang terjadi pada tim virtual startup. Metode yang digunakan adalah convergent parallel mixed-methods dengan menganalisa data kuantitatif dari kuesioner yang diisi 156 tim virtual startup dan data kualitatif dari interviu yang dilakukan pada lima pemimpin tim virtual startup. Hasil studi menunjukkan bahwa tim berinteraksi secara mixed virtual, yaitu interaksi tim tidak sepenuhnya dilakukan secara daring. Tim virtual startup di masa pandemi telah melakukan interaksi tatap muka langsung sebelum berinteraksi virtual dan/atau dapat melakukan pertemuan tatap muka di masa pandemi, dengan memperhatikan protokol kesehatan. Interaksi mixed virtual ini menciptakan hubungan yang informal yang dapat membuat startup bertahan di masa pandemi.